Сучасний стан формування та використання фінансових ресурсів місцевих бюджетів України - Яковченко, Д. М.; Насібова, Ольга Вікторівна (ТОВ "ДКС Центр, 2018)
В статті висвітлюється сучасний стан формування та використання фінансових ресурсів місцевих бюджетів , з урахуванням внесених змін до бюджетного та податкового законодавства, проведено аналіз доходної частини та видаткової частини бюджету. На основі проведеного дослідження визначено проблеми та шляхи зміцнення фінансової бази органів місцевого самоврядування. Встановлено, що за умови вирішення законодавчих, організаційних та соціальних проблем місцеві бюджети, зможуть мати достатній обсяг коштів на виконання делегованих повноважень. Актуальність даної теми полягає в тому що, дослідивши джерела формування дохідної бази та фактори які впливають на видаткову частину бюджетів ми зможемо визначити певні закономірності та спрогнозуємо проблеми які можуть виникнути у майбутньому. Також проаналізовано які функції впливають на формування дохідної частини місцевого бюджету, розраховано яку частку за останні роки займають доходи та видатки місцевих бюджетів в частині зведеного бюджету України. Розраховано приріст, щодо попередніх років, видаткової та доходної частин за аналізований період та сформульовані певні висновки. Проаналізовано погляди вітчизняних вчених щодо змісту поняття "місцевий бюджет", подано авторське бачення поняття "місцевий бюджет", а також розглянуто питання удосконалення теоретичних аспектів щодо формування місцевих бюджетів.

The article covers the current state of formation and use of financial resources of local budgets, taking into account the changes made to the budget and tax legislation, an analysis of the revenue part and the expenditure part of the budget. On the basis of the research, the problems and ways of strengthening the financial base of local self-government bodies were identified. It is established that, subject to the resolution of legislative, organizational and social problems, local budgets will be able to have sufficient funds to carry out delegated powers. The urgency of this topic is that by investigating the sources of the formation of the income base and factors that affect the expenditure part of the budgets, we can determine certain laws and predict the problems that may arise in the future. It also analyzes what functions affect the formation of the revenue part of the local budget, which part has been calculated in recent years by the revenues and expenditures of local budgets in the part of the consolidated budget of Ukraine. The growth is calculated for previous years, expenditure and revenue parts for the analyzed period and formulated certain conclusions. The views of domestic scientists on the content of the concept of "local budget" are analyzed, author's vision of the concept "local budget" is presented, as well as issues of improvement of theoretical aspects concerning the formation of local budgets. The scientific novelty of the results is in-depth analysis of the formation and use of funds, provisions on optimizing local budgets. Substantive provisions: 1) improved: scientific approach to the analysis of income and expenditure parts of local budgets, which also makes it possible to significantly mitigate the impact of certain shortcomings in the implementation of administrative and territorial reform in Ukraine and to strengthen the financial bases of local budgets; 2) was further developed: the definition of the nature of the category "local budgets" as a complex concept, which, unlike the existing approaches, covers the process of distribution of powers between levels of government in relation to the formation of financial resources, provides an opportunity to accumulate and accumulate such amount of financial resources in local budgets, which provides strengthening of the financial base of local self-government bodies.
Current state of formation and use of financial resources of local budgets of Ukraine
Keywords: місцеві бюджети; фінансові ресурси; поняття; доходна частина бюджету; видаткова частина бюджету